The Influence of Brotowali Extract (Tinospora crispa (L.) Miers.)onCholesterol Blood Level of Rattus norvegicus with High Cholesterol Intake - Lazuardi, Dicky Maulana; Nurwati, Ida; Wiyono, Nanang (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Introduction: Coronary Heart Disease is the disease that often suffered by Indonesian people which known with high cholesterol rate.Brotowaliâs stem contains saponin, flavonoid and polifenol, which potential to inhibit bloodÂ total cholesterolincrease. The research is for to know more the influence of the content of the brotowaliâs stem extract against total blood cholesterol levels. Method: ThisÂ research is as experimental laboratoric research with Randomized Controlled Trial design that post-test only control group design, have done in Histology Laboratorium of the Sebelas Maret University, Surakarta. The subject are 32 male white rats, Wistar strain, aged 2 months, weighing more or less than 200 grams. Brotowaliâs stem extract made by using maceration method in Biological Pharmacy Laboratory, Pharmacy Faculty, Gadjah Mada University. The rat were divided randomly into 4 groups, each group consisting of 8 rats. In the negative control group was only given regular feed, propiltiourasil (PTU) and distilled water, the positive control group was given 5 gramduck egg yolk per 4,5 ml of aquadest, regular feed, PTU and distilled water. Whereas in the treatment group I and II was given 5 gram/4,5 ml of duck egg yolk suspense, regular feed, PTU, water and given 50 mg/200 gr and 100 mg/200gr extract of the brotowaliâs stem. Rats were fasted during 12 hours and then their blood cholesterol levels checked after the 21 days treatment period. The sample measured with TMS 24i Premium spectrophotometer with 600 nm wave. The data were analyzed by one-way ANOVA with SPSS for Windows version 22. Result:Total cholesterol levels of negative control group is 91,00Â±19,46 mg/dl,on the positive control group is 104,12Â±13,66 mg/dl,on treatment group I is 91,50Â±16,08 mg/dl and on treatment group 2 is 84,62Â±13,45 mg/dl.The result ofÂ one-way ANOVA test showed there is no significant total cholesterol blood level difference between 4 groups of rats with p=0,120. Conclusion:Brotowaliâs stem extract has not give an effect on total cholesterol blood levels of Rattus norvegicus with high cholesterol intake. Keywords: Brotowaliâs stem extract, total cholesterol, Rattus norvergicus Â